Straddling the Boundaries of the Zone of Tolerance: One District's Response to Rapid Demographic Change. Issue 7 (September 2019) - Grooms, Ain A.
Sewall County, located in metropolitan Atlanta, and its public school system experienced significant demographic change between 2000 and 2010. The population doubled, reaching more than 200, 000 residents, and its percentage of White residents fell by 25% to just more than 55%. Its public school system is now considered majority–minority. Using the zone of tolerance framework, which argues that there are boundaries within which community members will allow policies to be changed, this study will examine how school and district leaders in Sewall County, Georgia, responded to the racial and socioeconomic changes in their schools and community. Findings indicate that there were no new policies enacted in the district to address rapid demographic shift, and instead, the district, individual schools, and parents engaged in actions that fell within and outside the boundaries of Sewall's zone of tolerance.